Reduction of quality costs through mass customization - Khdier salman aithiab (Journal of Madenat Alelem University College, 2019)
The mass customizations is one of the new models that leads to quick response to customer requests customer participation in product or service design processes that meet their needs. The aim of this study is to reduce the cost of quality in the economic units through mass customization and to finish the costs of external and internal failure. The most important conclusion of the study is that the system of mass customization of modern means that will help the management of economic units to program their production according to the customer's desire and the most important conclusion The study reached is the need to adopt high-tech and high-tech systems, and then all costs of external and internal failure will be eliminated.